Business Feasibility Analysis In Coffee Shop Kedai Cokelat Kendari (A Study Of Four Indicators On The Marketing Aspect) - Yusna Yusna; Indrawan Tobarasi; Saasa Saasa; Komeyni Rusba; Andi Muh. Dzulfadli (Jurnal Administrasi Bisnis Fisipol Unmul, 2022)
This study aims to analyze business feasibility in terms of marketing aspects at Coffee Shop (Warkop) Kedai Cokelat Kendari which is focused on product share, market share, market strategy and forecasting indicators. This study used descriptive qualitative methods, research data sourced from interviews research informants, observations and secondary data from various literatures. The results show that in running its business Warkop Kedai Cokelat Kendari has implemented a product share strategy, market share, and market strategy indicators, but has not done forecasting indicator to predict various possibilities that will be faced by Warkop Kedai Cokelat in the future. Based on these results, it is concluded that Warkop Kedai Cokelat Kendari has not met the standard of business feasibility in terms of marketing aspects.